Fan driver replacement pada fraksinator sistem hydrocracking - Anwar, Zaki (TURBO [Tulisan Riset Berbasis Online], 2024)
This research examines the shift from steam turbines to electric motors for powering the fan drive in a hydrocracking unit's fractionator. While steam turbines have traditionally been valued for their high power output and versatility, they come with significant downsides, such as oil and steam leakage, complex maintenance needs, and low reliability due to wear and tear. Additionally, their long startup times can hinder productivity. To address these issues, the study evaluated the use of electric motors as an alternative. The findings revealed that electric motors, three-phase induction model such as the ILA7 131 and ILA7 166, offer benefits like simpler maintenance, higher reliability, and faster startup times. By adjusting the gear transmission ratio to 8.26 and 13.36, these motors can effectively meet the necessary fan torque and performance requirements, thereby improving the overall efficiency and reliability of the hydrocracking unit.